Intellectual Capital and Operational Efficiency of Listed Firms in Nigeria: The Moderating Role of Ownership Structure - Busari, Romoke (Disclosure: Journal of Accounting and Finance, 2025)
This study investigates the moderating role of ownership structure on the relationship between intellectual capital disclosure and operational efficiency in listed non-financial firms in Nigeria. Utilizing panel data from listed non-financial firms in Nigeria spanning from 2014 to 2023, the study employs an ex-post facto research design. Descriptive statistics, correlation analysis and Generalized Method of Moments (GMM) regression technique are employed to address endogeneity concerns and ensure robust estimations. Intellectual capital is proxy by human capital, structural capital and relational capital; operational efficiency is proxy by operating profit margin and asset turnover while control variables include firm size, leverage and firm age. Key findings reveal that the interaction between ownership structure and human capital has a significant positive effect on operational efficiency. However, the interaction between ownership structure and structural capital has a significant negative effect on operating profit margin; thus, ownership structure demonstrates a dual role. It enhances the positive effects of human and relational capital on profitability but diminishes structural capital's influence. The study concludes that ownership concentration can both facilitate and constrain the translation of intellectual capital into operational efficiency, depending on the capital component and efficiency measure.